Prognostic Factors of MS Conversion in Optic Neuritis - Marytery Fajardo; Jennifer P Rubin (Pediatric Neurology Briefs Publishers, 2015)
Investigators from Children's Hospital Aschaffenburg, Germany; University of Manchester, Manchester, United Kingdom; University Children's Hospital Tübingen, Tübingen, Germany; and other international centers studied prognostic factors in optic neuritis.